Grand Challenges in Transportation and Transit Systems - Kaewunruen, Sakdirat; Sussman, Joseph M.; Matsumoto, Akira (Frontiers in Built Environment, 2016)
Transportation and transit systems draw upon broad spectra of research fields due to the diversity and interconnectivity of transport modes, including road, rail, aviation, pipeline, maritime, or even aerospace. These systems have evolved over centuries to be considerably more efficient and environment-friendly for a wide range of customers. The fundamental principle “safety first” is still the key priority in most research today. However, thanks to extensive interface with various customers; research and innovation in practices have shifted from optimizing functional purposes and targets through each stage of life cycle toward modernization, reliability, resilience, and better quality of life. These initiatives additionally coincide with the grand challenges for engineering proposed by the National Academy of Engineering and the United Nations’ Millennium Development Goals (National Academy of Engineering, 2015).